Photon counting system with automated detection and selection of photodetector discrimination thresholds - Bobrovnikov, Sergei M.; Zharkov, Viktor I.; Zaitsev, N. G.; Nadeev, A. I.; Trifonov, D. A. (Proceedings of SPIE)
The paper considers a block diagram of a photodetection system based on a new version of the four-channel photon counter "PHCOUNT-4" used for precision lidar measurements of atmospheric temperature. The results of using the new capabilities of the analog part of the photon counting system, which makes it possible to automatically record the amplitude distribution of single-electron pulses of each of the photodetectors installed in the channels and determine the optimal discrimination threshold, are described. It is shown that setting the optimal discrimination thresholds makes it possible to achieve a small spread in the end-to-end quantum efficiency of each of the channels